2014
DOI: 10.1080/10640266.2014.981429
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Help-Seeking in Anorexia Nervosa: Patients’ Perspective of First Contact With Health Services

Abstract: In this study we explored circumstances, reflections, and reactions to first treatment contact in 34 women (aged 18-51) diagnosed with anorexia nervosa (AN) (DSM-IV). Using methods from grounded theory we identified how the meeting came about, what motivated the patients, and how they reacted to the conversation. The results suggest that (a) health care professionals need to demonstrate effective professional communication skills and proficient knowledge about eating disorders in early contacts; (b) treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 26 publications
3
49
0
1
Order By: Relevance
“…Another prominent barrier identified in the current review was denial, a lack of awareness or a failure to perceive the severity of the problem. This was consistent across included studies that examined clinical samples and at‐risk samples . Some of the included studies indicated that individuals with eating disorders do not necessarily consider their disordered eating behavior to be problematic which in turn prevents them from seeking help.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Another prominent barrier identified in the current review was denial, a lack of awareness or a failure to perceive the severity of the problem. This was consistent across included studies that examined clinical samples and at‐risk samples . Some of the included studies indicated that individuals with eating disorders do not necessarily consider their disordered eating behavior to be problematic which in turn prevents them from seeking help.…”
Section: Discussionsupporting
confidence: 59%
“…Included studies have shown that people with eating disorders are afraid of gaining weight, have a fear of losing the positive aspects of the eating disorder, and feel that they are not ready for change . Participants in these studies reported that their eating disorder was an important part of their identity and provided them with a sense of control . Consequently this had a negative impact on their help‐seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People with eating disorders (i.e., anorexia nervosa and bulimia nervosa) are often considered to have low motivation to change eating disorder behaviors (Colton & Pistrang, 2004;Leavey, Vallianatou, Johnson-Sabine, Rae, & Gunputh, 2011). One possible reason for this low motivation to change may be a sense of denial regarding whether behaviors are problematic or require intervention (Gulliksen, Nordbø, Espeset, Skårderud, & Holte, 2015;Reyes-Rodríguez, Ramírez, Davis, Patrice, & Bulik, 2013). Indeed, the core features of eating disorders can often be highly valued and perceived as functional, as the behaviors may provide a focus, coping mechanism or sense of control (Schmidt & Treasure, 2006;Schoen et al, 2012;Williams & Reid, 2010).…”
Section: Introductionmentioning
confidence: 99%